Comparison of efficacy of myringoplasty in dry and wet ears in chronic otitis media of tubotympanic type - Chandrashekar, Yogeshwar; Chandrashekar, Ravishankar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The objective of the study was to compare the outcome of myringoplasty in dry and wet ears in tubotympanic type of chronic otitis media (COM) with respect to graft uptake and hearing improvement. Methods: This is a prospective study done in department of ENT Bangalore Medical College and Research Institute during the study period of November 2014 to May 2016, wherein a total of 60 patients of tubotympanic type COM with 30 cases each of dry and wet ears, aged 15-60 years were included. The hearing impairment was assessed and recorded by pure tone audiometry (PTA). After obtaining informed written consent the patients underwent myringoplasty (temporalis fascia graft, underlay technique). Microbiological examination of discharge in wet ears was done and histopathology of the excised remnant TM analyzed in both groups. Both groups of patients were followed up for 3 months and assessed for graft uptake and hearing improvement. PTA was repeated at 3 months postoperatively. Results: Our study included 60 patients of tubotympanic type of COM with 30 cases each with dry and wet ears who underwent myringoplasty. Majority of our patients were in second decade in both the groups. There was slight female preponderance in our study with male to female ratio of 0.93:1. Discharge from ears in wet ears was mucoid in consistency and were culture negative. Histopathology of excised remnant TM in wet ears revealed evidence of inflammatory cells and vascularization within stroma of fibroblasts while these were absent in dry ear cases. The overall successful graft uptake following myringoplasty was 88.3% with 86.7% for wet ears and 90% for dry ears with no statistical significance (p value of 0.688>0.05) between the two groups. With respect to hearing improvement post-operatively there was significant hearing improvement in both the groups when compared to preoperative hearing with a mean hearing gain (dB) of 3.43±2.81 in wet ear cases to 3.85±3.05 in dry ear cases, but when compared between the two groups, there was no significant statistical difference (p value of 0.582>0.05). Conclusions: The outcome is equally good for myringoplasty in dry and wet ears in tubotympanic type of chronic otitis media with respect to graft uptake and hearing improvement.